Implementasi Program Kartu Indonesia Pintar Kuliah di Perguruan Tinggi Swasta - Eva Nur Laily Rohmah; Zuli Kasmawanto (Madani Jurnal Politik dan Sosial Kemasyarakatan, 2022)
Smart Indonesia Card-College Program is one of the government's policy efforts in improving the quality of human resources while preparing the nation's next generation to excel. Darul 'Ulum Lamongan Islamic University is one of the private universities that implements the KIP-Lecture Program in the 2020/2021 academic year. This article attempts to examine and analyze the implementation process of the KIP-Kuliah Program in Private Higher Education with a case study at the Islamic University of Darul 'Ulum Lamongan. The results showed that there were few obstacles in the communication process and student resources who did not comply with the rules, especially in collecting files so that it had an impact on the process of developing funds. The author provides suggestions for stakeholders, namely to facilitate student recipients of the KIP-Kuliah program with empowering trainings. Suggestions for the government to increase the quota because of public interest in obtaining KIP-Kuliah.